2019
DOI: 10.1039/c8sc05358h
|View full text |Cite
|
Sign up to set email alerts
|

Durable liquid-crystalline vitrimer actuators

Abstract: A vitrimer-based LCE actuator subtly mitigates the conflict between processability and actuation durability by reducing the catalyst content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 38 publications
2
58
0
Order By: Relevance
“…Vitrimers are able to change their topological structure due to the exchange reactions under certain external stimuli. To date, most of the monodomain LCPs with exchangeable links were prepared based on transesterification [45][46][47], transcarbamoyalation [48], boronic-ester bond [49], disulfide [50,51], and allyl sulfide groups [52][53][54]. Summarized in Figure 2, Ji et al demonstrated that after programming the LCEs monodomain with the topological network rearrangement were facilitated by thermo-induced transesterification.…”
Section: Strategy For Preparation Of Monodomain Lcpsmentioning
confidence: 99%
“…Vitrimers are able to change their topological structure due to the exchange reactions under certain external stimuli. To date, most of the monodomain LCPs with exchangeable links were prepared based on transesterification [45][46][47], transcarbamoyalation [48], boronic-ester bond [49], disulfide [50,51], and allyl sulfide groups [52][53][54]. Summarized in Figure 2, Ji et al demonstrated that after programming the LCEs monodomain with the topological network rearrangement were facilitated by thermo-induced transesterification.…”
Section: Strategy For Preparation Of Monodomain Lcpsmentioning
confidence: 99%
“…In all of the previous systems, as long as thermally triggered bond exchange exists, the risk of actuation loss and shape distortion always exists at work and in storage, which is not satisfactory for applications that demand creep resistance at elevated temperature. The unwanted thermally induced bond exchange can be slowed down, but it cannot be eliminated …”
Section: Introductionmentioning
confidence: 99%
“…However, as for the aligned actuator in which TMA‐DMSiO had not been deactivated, degradation of thermal actuation was obviously observed after the first cooling–heating cycle (Supporting Information, Figure S17). Notably, our strategy to switch off network dynamics for attaining thermal and actuation stability is essentially different from the previous strategies that just slow down the bond exchange rate at high temperatures in LCEs . Our strategy directly eliminates the siloxane bond exchangeability in the network.…”
Section: Resultsmentioning
confidence: 98%